Bc+ formation from random charm and anti-bottom quarks in the quark-gluon plasma - Baoyi Chen; Liuyuan Wen; Yunpeng Liu (Physics Letters B, 2022)
We study the Bc+ production in Pb-Pb collisions at sNN=5.02 TeV. In the quark-gluon plasma (QGP) produced in heavy-ion collisions, heavy quarks make random motions with the energy loss. We employ the Langevin equations to study the non-equilibrium distributions of heavy quarks and the Instantaneous Coalescence Model (ICM) to study the hadronization process. Due to abundant charm and bottom quarks in the QGP, their coalescence probability is significantly enhanced compared with the situations in proton-proton collisions. We find that the final production of Bc+ is increased by the coalescence process, which makes the nuclear modification factor (RAA) of Bc+ larger than unit. Our model explains the experimental data well at semi-central and central collisions. The observation of RAA(Bc+)>1 is regarded as an evident and strong signal of the existence of the deconfined medium generated in heavy-ion collisions.